Bird responses to habitat change in the karst area of Bantimurung Bulusaraung National Park - Indra A.S.L.P. Putri; Bayu W. Broto; Fajri Ansari (Jurnal Penelitian Kehutanan Wallacea, 2017)
Birds are useful bioindicatorsto habitat changes. This study aims to determine the responses of birds to habitat change at Maros-Pangkep karst area, Bantimurung-Bulusaraung National Park. The research was carried out in three disturbance degrees (core-zone, wilderness-zone,and the community-gardens), which represents minimal, middle, and high interference level. A modifiedsquare-line method was used to observe vegetation of bird habitat. Point count method was used to observe bird population. Data of the bird habitat vegetation was analyzed using vegetation density. The difference of vegetation composition was analyzed using Sorensen-similarity index. Data of the bird was analyzed using abundance, and indexes of Shannon-Weinnerdiversity, Simpson dominance, Pielou evenness, and Margalef species richness. Significant differences between the numberof the individualbird weretested using one-way ANOVA, Tukey-Bonferroni test. The results showed that birds living in karst were sensitive to habitat changes. Birds responded through reducing the number of individuals and species, shifting the species of bird that has high importance value index from low tolerance species to high tolerance species. Birds also responded by shifting the feeding guild that has high important value index from frugivore to frugivore-insectivore and then to granivore, decreasing the number of bird species with large body size, reducing the number of bird species that need a special location to build nest. Considering that Maros-Pangkep Karst has vital roles, scientific values, and biodiversity richness, it is necessary to involve all stakeholders to maintain its sustainability, including the establishment of entire Maros-Pangkep Karst area as the karst-landscape area.